Revitalization of Kindergarten Landscape to Encourage Early Childhood Education in Rural Areas - Andardi, Faris Rizal; Cahyani, Rizki Amalia Tri; Rusdianto, Yunan (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This community service focuses on the revitalization of a kindergarten landscape in rural areas as an effort to stimulate the public’s interest in early childhood education. The upgraded kindergarten’s landscape is believed to increase students’ motivation and learning interest.Method: The methods employed in the study were based on the descriptive approach to identify the issues in the targeted areas. The data was collected using qualitative means which include interviews and field observations. The data was then analyzed to form the basis for decision-making and to choose the appropriate course of action to address the issues.Practical Applications: The revitalization of the kindergarten landscape plays a major role in the children’s learning experience. These spaces provide convenient outdoor activities and act as learning stimuli for the children to gain knowledge about nature. Furthermore, the appealing landscape could encourage the public to set their children in early childhood education.Conclusion: This community service aims to revitalize the kindergarten landscape to create convenient outdoor spaces and act as a learning aid for the student. This service succeeds in providing an improved landscape for the kindergarten which contributes to the broader student learning experience. The more appealing landscape gave the school a fresh look to entice the public interest in early childhood education.